Pengaruh Tunjangan Kinerja, Kompetensi, Dan Disiplin Terhadap Kinerja Pegawai Pada Kantor Kecamatan Campalagian Kabupaten Polewali Mandar - Syamsi, Samra; Ramly, Mansyur; Zakaria, Junaiddin (Jurnal Mirai Management, 2024)
This research was conducted with the aim of testing and analyzing the influence of performance allowances, competency and discipline on the performance of employees in Campalagian District, Polewali Mandar Regency, both partially and simultaneously. This research is a type of descriptive quantitative research. The sample consisted of 63 employees of the Campalagian District office, Polewali Mandar Regency. Data collection techniques use questionnaires, observation and documentation. The data analysis technique uses multiple regression analysis. The results of this research show that 1) performance allowances have a positive and significant effect on the performance of employees in Campalagian District, Polewali Mandar Regency. 2) Competence has a positive and significant effect on the performance of employees in Campalagian District, Polewali Mandar Regency. 3) Discipline has a positive and significant effect on the performance of employees in Campalagian District, Polewali Mandar Regency. And simultaneously performance allowances, competency and discipline influence the performance of employees in Campalagian District, Polewali Mandar Regency. Keywords : Discipline, Employee Performance, Competency, Employee Performance.